2013
DOI: 10.4314/ejesm.v6i6.7s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Climate Change on Rice Production in Niger State, Nigeria

Abstract: This study analyses the trend of climatic factors (rainfall, minimum and maximum temperature and humidity) in Niger state, Nigeria, as one of the major states contributing to the total rice output of the country. This study also describes the trend in rice production of Niger state and determined the factors affecting the output of rice in the state. Secondary data from 1981-2010 were used. The analytical tools used were descriptive analysis, unit root and co-integration. The result of the research reveals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 13 publications
0
14
1
1
Order By: Relevance
“…In fact, most of the previous studies have focused on temporal and spatial trends [22], magnitude and frequency of rainfall and runoff occurrence for various return periods [23], response patterns of hydrological parameters [24], effects of climate change [14] [25], and flood analysis [27].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most of the previous studies have focused on temporal and spatial trends [22], magnitude and frequency of rainfall and runoff occurrence for various return periods [23], response patterns of hydrological parameters [24], effects of climate change [14] [25], and flood analysis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one of the most serious long-term challenges to achieving sustainable rice yield in the state is climate change. Previous studies have shown that humidity and minimum temperature are the climatic factors that affect rice production in the area, such that 1% increase in humidity resulted in a 17% reduction in rice production in Niger state [9]. The gravity of the issues herein analysed reinforces the need for a mix-scale analysis anchored in descriptive statistics and Geographic Information Systems (GIS) mapping of rice yield trends essential in the design of a crop index.…”
Section: Introductionmentioning
confidence: 82%
“…This represents a severe drop in Niger state's rice yield. Following that, the rice yield once again moved up slowly by 407,200 tons, while the slow surge held steady till 2009 at 532,010 tons on a low pace, it still could not crack the 1997 high production levels [9]. The drop-off in production in the other years did not operate in a vacuum.…”
Section: Rice Productions Over the Years: The 1990smentioning
confidence: 99%
“…Such include, Auff hammer (2011), Ayinde et al (2013), Besir and Ceylan (2013), Ugwu (2013) and Scharticles (2014) among others. Auff hammer, (2011) used a combination of statistical and simulation methods to analyse impact of the changing monsoon rainfall pattern on rice production in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, Ayinde et al (2013) evaluated the effects of climate change on rice production in Niger State, Nigeria using analytical tools of descriptive analysis, unit root and co-integration. The result reveals humidity and minimum temperature as the most critical climatic factors for rice cultivation in the area.…”
Section: Introductionmentioning
confidence: 99%